Mimicry of formaldehyde as aldehyde: a potential and novel chemical compound to control storage pests - Syarifah Zulaikha S. A.; Yaakop S. (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
Tribolium castaneum is one of the most pervasive pests to threaten the storage of rice in Malaysia; thus, control methods are being studied to overcome this problem. The main objective of this study is to measure the efficacy of paint to attract T. castaneum. Based on preliminary results regarding olfactory responses, the formaldehyde compound in paint is highlighted as a potential and alternative method to be used as bait to trap the T. castaneum that infest rice storage warehouses. This result is likely due to the paint’s main element, formaldehyde, which releases a pungent smell and attracts the pests. Chemically, formaldehyde is a simpler form of aldehyde, with the formula CH2O. The idea to use paint in this study was inspired by the reports of warehouse workers who declared that insect pests are attracted to the paint that is stored in warehouses. Interestingly, this preliminary finding results in an interesting conclusion and a novel outcome in the field of stored product research. To this end, researchers recommend a paint or formaldehyde compound to serve as bait capable of attracting T. castaneum.